2020
DOI: 10.1007/s10875-020-00927-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immunosuppression and Autoimmune Disease on Severe Outcomes in Patients Hospitalized with COVID-19

Abstract: Immunosuppression (IS) and autoimmune disease (AD) are prevalent in patients with severe coronavirus disease 2019 (COVID-19), but their impact on its clinical course is unknown. We investigated relationships between IS, AD, and outcomes in patients hospitalized with COVID-19. Data on consecutive admissions for COVID-19 were extracted retrospectively from medical records. Patients were assigned to one of four cohorts, according to whether or not they had an AD (AD and NAD) or were immunosuppressed (IS and NIS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…have not yet found such an association (35,36). We found 21% higher odds of complicated hospitalizations among patients with IMIDs when considering the entire study population regardless of whether they were admitted.…”
Section: Discussionmentioning
confidence: 48%
“…have not yet found such an association (35,36). We found 21% higher odds of complicated hospitalizations among patients with IMIDs when considering the entire study population regardless of whether they were admitted.…”
Section: Discussionmentioning
confidence: 48%
“…It was found that fewer patients with IMIDs receiving cytokine blocker therapy (which do not deplete B cells) had SARS-CoV-2 IgG seroconversion than patients without such therapy and healthy individuals 53 , suggesting that cytokine inhibitors at least partially protect against severe SARS-CoV-2 infection. Conversely, another study ( n = 789 patients) examined the effects of immunosuppression on COVID-19 in patients with autoimmune and chronic inflammatory diseases 90 . Relative to the control cohort (without autoimmune diseases and immunosuppressive therapy), patients with immunosuppressive therapy in autoimmunity had a markedly reduced risk of severe acute respiratory distress syndrome.…”
Section: Immunosuppressants and Biologics In Ibdmentioning
confidence: 99%
“…Despite the initial concerns regarding susceptibility to SARS-CoV-2 infection among patients with AARD, a growing body of data -mostly observational in nature-is reassuring and detects similar or slightly elevated risk for serious/fetal COVID-19 compared to the general population [ [2] , [3] , [4] , [5] , [6] ]. Of interest the use of immunosuppressive therapy and adherence to treatment has been shown to be associated with lower frequency of COVID-19 related symptoms [ 5 ], lowering the risk for developing severe acute respiratory distress syndrome (ARDS) [ 7 ]. Small series and case reports of patients with AARD infected with SARS-CoV-2 revealed that the treatment with tumor necrosis factor a (TNFα) antagonists, anakinra or tocilizumab develop a mildest form of SARS-CoV-2 infection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%